The Effectiveness of Developing Problem-Solving Oriented Digital E-Modules on Theme 7: Events in Life for Grade V Elementary School - Sulfiana Firman; Nurlina; Rahmawati; Ma’ruf; Muh Erwinto Imran (South Sulawesi Education Development (SSED), 2024)
This research aims to produce instructional materials in the form of a problem-solving oriented digital e-module for fifth-grade elementary school students on the theme